2023
DOI: 10.1101/2023.03.22.533872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of the stress peptides PACAP and CRF on sleep architecture in mice

Abstract: Stress produces profound effects on behavior, including persistent alterations in sleep patterns. Here we examined the effects of two prototypical stress peptides, pituitary adenylate cyclase-activating polypeptide (PACAP) and corticotropin-releasing factor (CRF), on sleep architecture and other translationally-relevant endpoints. Male and female mice were implanted with subcutaneous transmitters enabling continuous measurement of electroencephalography (EEG) and electromyography (EMG), as well as body tempera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…Based on prior evidence that PACAP relates to hyperarousal in PTSD, digital phenotyping metrics of arousal would be worth examination in future studies. Recent work in mice shows that acute administration of PACAP can regulate sleep architecture captured using subcutaneous detectors (Foilb et al, 2024 ), although future work is needed to precisely model the types of long-term changes in PACAP function and sleep that might be seen in people with PTSD. Nonetheless, further research is needed to test the hypothesis that structural changes of the EC may serve as an intermediary factor influencing the relationship between PACAP and lower functional connectivity of the amygdala and hippocampus in PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior evidence that PACAP relates to hyperarousal in PTSD, digital phenotyping metrics of arousal would be worth examination in future studies. Recent work in mice shows that acute administration of PACAP can regulate sleep architecture captured using subcutaneous detectors (Foilb et al, 2024 ), although future work is needed to precisely model the types of long-term changes in PACAP function and sleep that might be seen in people with PTSD. Nonetheless, further research is needed to test the hypothesis that structural changes of the EC may serve as an intermediary factor influencing the relationship between PACAP and lower functional connectivity of the amygdala and hippocampus in PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is characterised by intrusion, avoidance, negative emotions, and hyperarousal symptoms after exposure to severe trauma (Ressler et al, 2022 ). Pituitary adenylate cyclase-activating polypeptide (PACAP) is a well-established neuromodulator of stress and arousal (Hammack & May, 2015 ), is involved in the secretion and production of corticotropin-releasing hormone (Agarwal et al, 2005 ; Boucher et al, 2021 ; Stroth & Eiden, 2010 ), stress-related sleep disturbance in mice (Foilb et al, 2024 ), and has been associated with hyperarousal symptoms of PTSD (Ressler et al, 2011 ). Stress-induced morphological alterations of the medial temporal lobe (MTL), including changes in amygdala and hippocampal volume, are implicated in PTSD (Shin et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Boys had longer sleep latency, and worse sleep efficiency than girls on Saturday nights ( Hrozanova et al, 2023 ). In exploring the effects of pituitary adenylate cyclase-activating polypeptide (PACAP) and corticotropin-releasing factor (CRF) on sleep structure, the researchers found that at baseline, male mice spent more time in NREM sleep and less time in wake than female mice ( Foilb et al, 2023 ). Only male mice were used in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments designed specifically to examine how fear conditioning affects sleep patterns, mice were implanted with wireless transmitters (HD-X02; Data Sciences International [DSI], St. Paul, MN) to enable continuous collection of EEG (electroencephalography) and EMG (electromyography) data, as described 31,[46][47][48] . Mice were anesthetized via intraperitoneal (IP) injections of 100 mg/kg ketamine/10 mg/kg xylazine mixed in saline.…”
Section: Sleep Transmitter Surgerymentioning
confidence: 99%
“…In parallel, we examined the effects of our sleep deprivation regimen on expression of mRNA encoding brain-derived neurotropic factor (BDNF), molecule implicated in neuroplasticity, in brain areas implicated in the development, expression, and extinction of fear-related behaviors 17,25,26 . Given the well-characterized sex differences in baseline sleep parameters [27][28][29][30][31] , interactions between sleep and gonadal hormones 28,30,[32][33][34][35][36] , and the prevalence of trauma-related illnesses such as PTSD [37][38][39][40][41][42][43][44] , we designed the studies to enable qualitative and quantitative comparisons between males and females. Our findings show that delayed sleep deprivation can reduce expression of conditioned fear in both sexes, and raise the possibility that the effects of this regimen are not due to disruption of memory consolidation but instead caused by BDNF-mediated neuroadaptations within the BLA that actively suppress expression of fear.…”
Section: Introductionmentioning
confidence: 99%